Diurnal patterns of objectively measured sedentary time and interruptions to sedentary time are associated with glycaemic indices in type 2 diabetes. Issue 11 (November 2020) - Paing, Aye C.; McMillan, Kathryn A.; Kirk, Alison F.; Collier, Andrew; Hewitt, Allan; Dunstan, David; Owen, Neville; Chastin, Sebastien F.M.
Abstract: Objectives: To investigate diurnal patterns of sedentary time and interruptions to sedentary time and their associations with achievement of pre-meal glucose, post-meal glucose, bedtime glucose and the dawn phenomenon targets and with duration of hypoglycaemia, euglycaemia, hyperglycaemia and above target range. Design: Intensive longitudinal study. Methods: In 37 adults with type 2 diabetes, the FreeStyle Libre and activPAL3 were used to monitor glucose and sedentary time and interruptions to sedentary time in the morning (07:00–12:00), afternoon (12:00–17:00) and evening (17:00–23:00) for 14 days. Diurnal patterns of sedentary behaviour and associations with glycaemic indices were assessed using repeated measures ANOVA and linear regressions. Results: Sedentary time was significantly higher in the evening (43.47 ± 7.37 min/h) than the morning (33.34 ± 8.44 min/h) and afternoon (37.26 ± 8.28 min/h). Interruptions to sedentary time were significantly lower in the evening (2.64 ± 0.74 n/h) than the morning (3.69 ± 1.08 n/h) and afternoon (3.06 ± 0.87 n/h). Sedentary time in the morning and afternoon was associated with lower achievement of the dawn phenomenon target. Sedentary time in the evening was associated with lower achievement of post-lunch glucose target. Interruptions to sedentary time in the morning and afternoon were associated with higher achievement of pre-dinner glucose target. Interruptions to sedentary time in the evening showed beneficial associations with achievement of post-dinner glucose and bedtime glucose targets and euglycaemia. Conclusions: Prolonged sedentary behaviour is high in the evening. Interruptions to sedentary time, particularly in the evening, have beneficial associations with glycaemic indices. Interventions targeting interruptions to sedentary time in the evening may be more clinically relevant.